Cosmological information from quasar-galaxy correlations induced by weak lensing - Ménard, Brice; Bartelmann, Matthias (Arxiv, 2014)
The magnification bias of large-scale structures, combined with galaxy biasing, leads to a cross-correlation of distant quasars with foreground galaxies on angular scales of the order of arc minutes and larger. The amplitude and angular shape of the cross-correlation function w_QG contain information on cosmological parameters and the galaxy bias factor. While the existence of this cross-correlation has firmly been established, existing data did not allow an accurate measurement of w_QG yet, but wide area surveys like the Sloan Digital Sky Survey now provide an ideal database for measuring it. However, w_QG depends on several cosmological parameters and the galaxy bias factor. We study in detail the sensitivity of w_QG to these parameters and develop a strategy for using the data. We show that the parameter space can be reduced to the bias factor b, Omega_0 and sigma_8, and compute the accuracy with which these parameters can be deduced from SDSS data. Under reasonable assumptions, it should be possible to reach relative accuracies of the order of 5%-15% for b, Omega_0, and sigma_8. This method is complementary to other weak-lensing analyses based on cosmic shear.
Gesehen am 27.09.2017